2012
DOI: 10.1055/s-0031-1291008
|View full text |Cite
|
Sign up to set email alerts
|

Lithiation and Substitution of N′-(ω-Phenylalkyl)-N,N-dimethylureas

Abstract: Lithiation of N′-phenethyl-N,N-dimethylurea with three equivalents of tert-butyllithium in anhydrous tetrahydrofuran at -78°C takes place on the nitrogen and on the side-chain of the CH 2 next to the phenyl ring (α-lithiation). The 2-lithio isomer can be obtained via bromine-lithium exchange of N′-2-(2-bromophenyl)ethyl-N,N-dimethylurea using methyllithium followed by tertbutyllithium in tetrahydrofuran at -78°C. The lithium reagents thus obtained react with various electrophiles to give the corresponding subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…Many convenient processes have been reported for the production of substituted ureas [6][7][8][9][10][11]. Aromatic ureas can be substituted efficiently via lithiation chemistry [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Many convenient processes have been reported for the production of substituted ureas [6][7][8][9][10][11]. Aromatic ureas can be substituted efficiently via lithiation chemistry [12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Various efficient procedures for the synthesis of aromatic ureas are known [6][7][8][9][10][11]. Aromatic ureas can be easily modified via treatment with lithium reagents followed by reactions with electrophiles, a methodology we have used in the last few years [12][13][14][15][16]. The asymmetric unit contains one molecule of C 10 H14N 2 O 2 .…”
Section: Commentmentioning
confidence: 99%
“…We now report that lithiation can be controlled to give either ring or side-chain substitution, depending on the protocol used. 3-Substituted pyridines 4-6 were synthesized, based on a literature procedure for analogous compounds, 9,10 ride, di-tert-butyl dicarbonate or dimethylcarbamoyl chloride, respectively (Scheme 2). Initially, N-(pyridin-3-ylmethyl)pivalamide (4) was treated with n-butyllithium (2.2 equiv) in anhydrous tetrahydrofuran at -78°C for two hours to form first the monolithium compound 7 (Scheme 3) and then perhaps one or more dilithium species.…”
Section: Scheme 1 Lithiation Of Substituted N-(pyridinylmethyl)aminesmentioning
confidence: 99%
“…[3][4][5] In our own studies 6 we have investigated selective lithiation of various benzyl-and phenylethylamine derivatives and shown that the site of lithiation depends on any substituent groups, the nature of the lithium reagent, and the reaction conditions. [7][8][9][10][11][12] We have applied such processes in the preparation of substituted heterocycles. [13][14][15] Heterocyclic compounds are of great importance since they represent the core unit of numerous important products.…”
mentioning
confidence: 99%